Trajectories of heart failure self-care management and changes in quality of life. (December 2015) - Lee, Christopher S; Mudd, James O; Hiatt, Shirin O; Gelow, Jill M; Chien, Christopher; Riegel, Barbara
Introduction: Heart failure patients vary considerably in their self-care management behaviors (i.e. recognizing and responding to symptoms). The goal of this study was to identify unique patterns of change in heart failure self-care management and quantify associations between self-care management and quality of life (HRQOL) over time. Methods: A prospective cohort study among adults with symptomatic heart failure was designed to measure changes in self-care management (Self-care of Heart Failure Index) and HRQOL (Kansas City Cardiomyopathy Questionnaire) over six months. Growth mixture modeling was used to identify unique trajectories of change in self-care management. Results: The mean age ( n =146) was 57 years, 70% were male, and 41% had class II heart failure. Two trajectories of self-care management were identified (entropy = 0.88). The larger trajectory (73.3%) was characterized by a significant decline in self-care management over time and no change in HRQOL. The smaller trajectory (26.7%) was characterized by marked improvements in self-care management and HRQOL. Changes in heart failure self-care management occurred in the absence of change in routine self-care maintenance behaviors, functional classification, and physical and psychological symptoms. Patients with greater physical symptoms at enrollment (odds ratio (OR) =1.04, p =0.037), larger left ventricles (OR=1.50, p =0.044), and ischemic heart failure (OR=3.84, p =0.014) were more likely to have the declining trajectory of self-care management. Higher levels of depression at enrollment were associated with reduced odds of having a decline in self-care management over time (OR=0.85, p <0.001). Conclusions: There are unique and clinically-relevant trajectories of change in heart failure self-care management that are associated with differences in HRQOL.